Why startups fail and how yours can succeed - Feinleib, David (Apress, 2011)
Why Startups Fail can help you beat the odds and avoid the pitfalls and traps that lead to early startup death. It's easy to point to successes like Apple, Google, and Facebook. But the biggest lessons can come from failure. What decisions were made, and why? What would the founders have done differently? How did one company become a billion-dollar success while another with a better product and in the same market fail? Drawing on personal experience as well as the wisdom of the Silicon Valley startup community, serial entrepreneur, venture capitalist, and blogger Dave Feinleib analyzes companies that have come and gone.In short, powerful chapters, he reveals the keys to successful entrepreneurship: Excellent product/market fit, passion, superb execution, the ability to pivot, stellar team, good funding, and wise spending. In Why Startups Fail, you'll learn from the mistakes Feinleib has seen made over and over and find out how to position your startup for success. Why Startups Fail: Shows venture-backed startups and boot-strappers alike how to succeed where others fail.Is equally valuable for companies still on the drawing board as well as young firms taking their first steps.Takes you through the key decisions and pitfalls that caused startups to fail and what you can learn from their failures.Covers the critical elements of entrepreneurial success.